Pelatihan Pembuatan Media Pembelajaran Dengan Pendekatan Metakognitif Berbantuan Canva Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Sekolah Dasar - Kartika Yuni Purwanti; lisavirdinartiputra; lisa virdinarti putra (Universitas Nusantara PGRI Kediri, 2022)
This service aims to determine the effect of Canva-assisted learning media on the problem-solving abilities of fourth grade elementary school students on KPK and FPB materials. The population in this service is students of SD N 2 Ampel and students of SD N 3 Urutsewu who are still in one cluster, then for the samples in this service are 4th grade students of SD N 2 Ampel and 4th grade students of SD N 3 Urutsewu. The results of the service show that there is an effect of using Canva-assisted learning media on the problem-solving abilities of fourth grade students on the KPK and FPB material, as evidenced by a significance level of 0.011 <0.05 using a simple linear regression test. The results of this service can be concluded that the Canva-assisted learning media has an effect on the problem-solving abilities of fourth grade students on the KPK and FPB material